2007
DOI: 10.1158/0008-5472.can-06-2760
|View full text |Cite
|
Sign up to set email alerts
|

Selective Targeting and Potent Control of Tumor Growth Using an EphA2/CD3-Bispecific Single-Chain Antibody Construct

Abstract: The EphA2 receptor tyrosine kinase is frequently overexpressed and functionally altered in malignant cells and thus provides opportunities for selective targeting of tumor cells.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 45 publications
5
59
0
Order By: Relevance
“…19 Meanwhile, instead of increasing the killing potency of T cells, higher E:T ratios appeared to only accelerate the T cell killing process. 19,23,4952 Consistently, the data we analyzed also suggested that the higher E:T ratios only accelerate the T cell killing process (τ), but do not affect the intrinsic potency value (EC 50 ). Our model used two exponential functions to correlate both effector cell concentrations (k τ1 ) and target-to-effector cell ratios (k τ2 ) to τ.…”
Section: Discussionsupporting
confidence: 81%
“…19 Meanwhile, instead of increasing the killing potency of T cells, higher E:T ratios appeared to only accelerate the T cell killing process. 19,23,4952 Consistently, the data we analyzed also suggested that the higher E:T ratios only accelerate the T cell killing process (τ), but do not affect the intrinsic potency value (EC 50 ). Our model used two exponential functions to correlate both effector cell concentrations (k τ1 ) and target-to-effector cell ratios (k τ2 ) to τ.…”
Section: Discussionsupporting
confidence: 81%
“…The gene encoding the HER2-binding affibody molecule was recovered from a vector containing a (Z HER2:342 ) 2 construct previously described by Orlova et al [30]. The vector was first restricted with endonucleases AccI and NotI, followed by ligation of a gene fragment (containing an SfiI restriction site) encoding the (GGGGS) 3 linker. The gene encoding the EGFR-binding affibody molecule was recovered from a vector containing a Z EGFR:1907 construct previously described by Friedman et al [31].…”
Section: Dna Constructionsmentioning
confidence: 99%
“…The gene encoding the EGFR-binding affibody molecule was recovered from a vector containing a Z EGFR:1907 construct previously described by Friedman et al [31]. A gene fragment (containing an SfiI restriction site) encoding the (GGGGS) 3 linker was introduced to the vector by amplifying the Z EGFR:1907 fragment with specific primers introducing the linker, followed by PstI/AccI and SfiI/AccI restriction and ligation. A second affibody gene construct was introduced head-to-tail, giving a vector encoding the (Z EGFR:1907 ) 2 with a N-terminal (GGGGS) 3 linker fragment.…”
Section: Dna Constructionsmentioning
confidence: 99%
See 2 more Smart Citations